Case report: retrograde approach for cto lesions: serial case - Oktaviono, Yudi Her (Folia Medica Indonesiana, 2017)
Chronic total occlusion recanalization still represents the final frontier in percutaneous coronary intervention. Successful revascularization is associated with improved long-term survival, reduced symptoms, improved left ventricular function and reduced need for coronary bypass surgery. Retrograde chronic total occlusion recanalization has recently become an essential complement to the classic antegrade approach. Retrograde approach through the collateral channel has been recently proposed and has the potential to improve the success rate of percutaneous coronary intervention (PCI) in chronic total occlusion (CTO) lession of the coronary arteries. We report several cases of successful CTO recanalization procedure using retrograde approach in Soetomo Hospital.